Between structural change and local agency in the palm oil sector: Interactions, heterogeneities and landscape transformations in the Brazilian Amazon. (October 2019) - Brandão, Frederico; de Castro, Fabio; Futemma, Célia
Abstract: Looking beyond a normative analysis of oil palm expansion, this paper offers a nuanced analysis of landscape transformations in the Brazilian Amazonian region of Tomé-Açu. Based on quantitative and qualitative data deriving from interviews with key stakeholders, focus groups and surveys with smallholders and migrant workers, contextualized and cross-checked with observations between 2011 and 2017 and secondary sources, we discuss the processes and outcomes of Brazil's Sustainable Oil Palm Production Program (SPOPP). Despite its participatory component and innovative design, simultaneously tackling environmental, economic and social dimensions, the program underwent rapid structural change and suffered from discontinuity. A new boom and bust cycle emerged in the region, however, both "boom" and "bust" periods were marked by mixed outcomes. Notwithstanding the current governance shift characterized by absent state, reduced participation and disinvestment, local agency has been able to reorganize the sector on the ground and a transformed landscape emerged. However, under the current setting if expansion recommences there is no guarantee the sector will be able to avoid many of the socio-environmental problems experienced in the past. Highlights: SPOPP is an example of the emergence of participatory governance modes in the Brazilian Amazon. SPOPP triggered a new boom and bust cycle in the researched region. Outcomes of both cycles were mixed, from euphoria and criticism to disenchantment and reorganization. Despite state withdrawal and reduced participatory governance the sector reconfigured under local and global drivers. If expansion recommences there are several socio-environmental risks under the current governance shift.